ANALISIS HASIL BELAJAR SISWA PADA MATERI BARISAN DAN DERET DALAM MASALAH KONTEKSTUAL - Roszana Isabella; Suryanti; Riki Suliana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study is to describe students’ learning outcomes in solving problems involving arithmetic sequences and series. The method used is a case study with a descriptive qualitative approach. The research subjects included 13 students from the 11th grade, selected using purposive sampling, with 3 students chosen to represent each of the three ability categories (high ability, moderate ability, and low ability). The data were analyzed using the theory proposed by Miles et al. (2014), which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that students in the high-ability category demonstrate strong comprehension and analytical skills. Students in the moderate-ability category were found to be quite capable of explaining their choice of strategies and providing sound solutions. Students in the low-ability category struggled with understanding, solving, and analyzing problems involving arithmetic sequences and geometry.